A different kind of pain: affective valence of errors and incongruence*. Issue 5 (4th July 2019) - Ivanchei, Ivan; Begler, Alena; Iamschinina, Polina; Filippova, Margarita; Kuvaldina, Maria; Chetverikov, Andrey
ABSTRACT: People hiss and swear when they make errors, frown and swear again when they encounter conflicting information. Such error- and conflict-related signs of negative affect are found even when there is no time pressure or external reward and the task itself is very simple. Previous studies, however, provide inconsistent evidence regarding the affective consequences of resolved conflicts, that is, conflicts that resulted in correct responses. We tested whether response accuracy in the Eriksen flanker task will moderate the effect of trial incongruence using affective priming to measure positive and negative affect. We found that responses to incongruent trials elicit positive affect irrespective of their accuracy. Errors, in turn, result in negative affect irrespective of trial congruence. The effects of conflicts and errors do not interact and affect different dimensions of affective priming. Conflicts change the speed of evaluative categorisation while errors are reflected in categorisation accuracy. We discuss the findings in light of the "reward value and prediction" model and the "affect as a feedback for predictions" framework and consider the possible mechanisms behind the divergent effects.